2022
DOI: 10.1186/s13024-022-00550-y
|View full text |Cite
|
Sign up to set email alerts
|

LILRB2-mediated TREM2 signaling inhibition suppresses microglia functions

Abstract: Background Microglia plays crucial roles in Alzheimer’s disease (AD) development. Triggering receptor expressed on myeloid cells 2 (TREM2) in association with DAP12 mediates signaling affecting microglia function. Here we study the negative regulation of TREM2 functions by leukocyte immunoglobulin-like receptor subfamily B member 2 (LILRB2), an inhibitory receptor bearing ITIM motifs. Methods To specifically interrogate LILRB2-ligand (oAβ and PS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…In addition, by administering the anti-LILRB4 mAb ZM3.1 to a transgenic mouse model with Aβ accumulation expressing human LILRB4 in microglia, we decreased Aβ plaque load by enhancing microglial responses to Aβ. Earlier research indicated that another inhibitory LILR family receptor, LILRB2, binds to Aβ, suppresses TREM2 signaling, and plays a role in neurodegeneration, suggesting that blocking LILRB2 could be a potential therapeutic approach in AD ( 29 , 30 ). LILRB4 appears to act through a mechanism different from that of LILRB2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, by administering the anti-LILRB4 mAb ZM3.1 to a transgenic mouse model with Aβ accumulation expressing human LILRB4 in microglia, we decreased Aβ plaque load by enhancing microglial responses to Aβ. Earlier research indicated that another inhibitory LILR family receptor, LILRB2, binds to Aβ, suppresses TREM2 signaling, and plays a role in neurodegeneration, suggesting that blocking LILRB2 could be a potential therapeutic approach in AD ( 29 , 30 ). LILRB4 appears to act through a mechanism different from that of LILRB2.…”
Section: Discussionmentioning
confidence: 99%
“…LILRB2, which recognizes MHC class I, was found to bind Aβ, and its mouse homolog, PIRB, was shown to contribute to AD neuropathology ( 29 ), suggesting that blockade of LILRB2 function may be therapeutically beneficial in AD. Another study proposed that LILRB2 and TREM2 are cross-linked through shared ligands like oligomeric Aβ and phosphatidylserine ( 30 ) and that antibody-mediated blockade of LILRB2 enhances TREM2 signaling. Moreover, genetic studies have found DNA polymorphisms within the LILRB2 and LILRA2 genes associated with AD and amyotrophic lateral sclerosis, respectively, corroborating a link between the LILR region and susceptibility to neurodegeneration ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…These low-MW and high-MW AbOs were determined by Hu et al 12 as Ab42 oligomers with MWs of 10-15 kDa (about 2-4 mer) and 50-100 kDa (about 14-48 mer) and mixed with a large number of monomers, 12 indicating that the affinity is dependent on the AbO MW and that high-MW AbO exhibits the higher affinity with the LDD receptor. Zhao et al 36 also reported a strong binding between biotinylated AbO and LilrB2, with a dissociation constant of 6.93 Â 10 À8 M. Moreover, Smith et al 37 found that biotinylated oligomers (4.23 Â 10 À8 M) had a higher affinity for LilrB2 than spherical oligomers (2.07 Â 10 À7 M). Taken together, the dissociation constants measured by the above experimental groups vary widely without any explanations.…”
Section: The Binding Capacity Of the Ldd Receptor With Abomentioning
confidence: 97%
“…35 It can be seen from the binding energy data (Table 1) that the Ab monomer has the weakest binding ability to the LDD receptor, with binding energy and dissociation constants of À6.1 kcal mol À1 and 3.3 Â 10 À5 M, which are consistent with the experimental observation that the LDD receptor does not bind to the Ab monomer. 11,12,36,37 When the AbO species at the SP1 had an intermolecular b-sheet content of less than 15%, the binding energies of AbO to LDD were À11.1 kcal mol À1 (D), À13.0 kcal mol À1 (T), À14.2 kcal mol À1 (Te), À14.9 kcal mol À1 (P), À16.1 kcal mol À1 (H) and À16.3 kcal mol À1 (O), respectively. When the AbO species at the SP2 had an intermolecular b-sheet content of more than 15%, the binding energies between the AbO and LDD receptor were À13.4 kcal mol À1 (D T ), À14.4 kcal mol À1 (T T ), À15.8 kcal mol À1 (Te T ), À16.1 kcal mol À1 (P T ), À17.1 kcal mol À1 (Te F ) and À20.5 kcal mol À1 (P T ), respectively.…”
Section: The Binding Capacity Of the Ldd Receptor With Abomentioning
confidence: 99%
“…www.science.org/doi/10.1126/scitranslmed.abq0095 Supplementary Materials and Methods Figs. S1 to S10 Data files S1 and S2 References (76)(77)(78)(79)(80)(81)(82)(83)(84)(85) View/request a protocol for this paper from Bio-protocol.…”
Section: Supplementary Materialsmentioning
confidence: 99%